Correction: Titanium aminophosphates: synthesis, characterization, antimicrobial and cytotoxicity studies. Issue 114 (1st December 2016) - Rajini, Anumula; Adepu, Ajay Kumar; Chirra, Suman; Venkatathri, Narayanan
Abstract : Correction for 'Titanium aminophosphates: synthesis, characterization, antimicrobial and cytotoxicity studies' by Anumula Rajini et al., RSC Adv., 2015, 5, 87713–87722.